Politics and conflict in governance and planning Theory and practice - Eraydin, Ayda; Frey, Klaus (New York Routledge, 2019)
Politics and Conflict in Governance and Planning offers a critical evaluation of manifold ways in which the political dimension is reflected in contemporary planning and governance. While the theoretical debates on post-politics and the wider frame of post-foundational political theory provide substantive explanations for the crisis in planning and governance, still there is a need for a better understanding of how the political is manifested in the planning contents, shaped by institutional arrangements and played out in the planning processes. This book undertakes a reassessment of the changing role of the political in contemporary planning and governance. Employing a wide range of empirical research conducted in several regions of the world, it draws a more complex and heterogeneous picture of the context-specific depoliticisation and repoliticisation processes taking place in local and regional planning and governance. It shows not only the domination of market forces and the consequent suppression of the political but also how political conflicts and struggles are defined, tackled and transformed in view of the multifaceted rules and constraints recently imposed to local and regional planning.

Switching the focus to how strategies and forms of depoliticised governance can be repoliticised through renewed planning mechanisms and socio-political mobilisation, Politics and Conflict in Governance and Planning is a critical and much needed contribution to the planning literature and its incorporation of the post-politics and post-democracy debate.
The political in governance and planning / Ayda Eraydin & Klaus Frey -- Crisis in planning theory : is the political a way out of the impasse in planning? / Ayda Eraydin & Tuna Tasan-Kok -- Planning and governance : towards radical political approaches / Rainer Randolph & Klaus Frey -- Multi-level power relations and planning conflicts in a "land of exception" : the case of the Sughereta di Niscemi Reserve in Sicily / Francesco Lo Piccolo, Filippo Schilleci & Vincenzo Todaro -- Engaging in politics of participation : managing power through action research / Anli Ataöv, Güliz Bilgin Altinöz & Neriman Sahin Güçhan -- Different understandings of "public interest" as a source of conflict : Portuguese spatial planning and practice / Joana Almeida & Fernando Nunes Da Silva -- The conflict between free market capitalism and social policies : Mexican housing policy / Alfonso Iracheta -- Shifting political conditions for spatial planning in the Nordic countries / Peter Schmitt & Lukas Smas -- Politicising the regional scale? : the politics of metropolitan governance in Germany, Canada and Brazil / Karsten Zimmermann -- Local welfare governance and social innovation : the ambivalence of the political dimension / Lavinia Bifulco & Maria Dodaro -- Politicisation of community development : universities as boundary objects / Anne Taufen -- A counter-movement to "place-less" power : planners as progressive place-based leaders / Robin Hambleton -- Scientific knowledge and decision-making in planning : understanding emotional aspects / Ilhan Tekeli -- Afterword : I am realistic. I expect miracles / Klaus Frey & Ayda Eraydin.
Includes bibliographical references and index.
Keywords: Political planning -- Case studies; Municipal government -- Case studies; Local government -- Case studies